دراسة تأثیر قوى المنافسة الخمسة لـ " "Porterعلى تنافسیة مؤسسات قطاع خدمة الهاتف النقال في الجزائر - بوعافیة عادل (Finance and Business Economies Review, 2018)
The aim of this study is to determine the impact of the five forces of competition on the competitiveness of the mobile service companies in Algeria، In this study, we found that competition in the industry is the only factor affecting the competitiveness of enterprises in the mobile service industry while the impact of other factors remains very limited and relatively weak.